The Influence of Self-Care Management on Blood Pressure Control in Hypertensive Patients: A Literature Review - Asseggaf, Syarifah Nurul Yanti Rizki Syahab; Zakiah, Mistika; Ulfah, Ridha; Putri, Triyana Harlia; Len, Jenny Firda; Qatrunnada, Aura (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hypertension, often referred to as the